2022
DOI: 10.1002/smll.202202033
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal Non‐Oxides as Electrocatalysts: Advantages and Challenges

Abstract: energy crisis. To satisfy this surging global energy demand, people often tend to use nonrenewable resources (coal, petroleum, natural gas, etc.), which generates an enormous amount of greenhouse gases, causing great obstacles for the development of a healthy human society. [1] To avoid such unhealthy environmental pollution, the use of renewable energy resources such as wind, solar, hydroelectric power, etc., over the past few years has served as the top priority to meet the global energy demand. The advancem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 575 publications
(974 reference statements)
1
51
0
Order By: Relevance
“…Transition metal carbides (TMCs), such as Mo 2 C, W 2 C, TiC, NbC, and VC, have broad application prospects in the field of energy storage and conversion due to their good thermal stability, mechanical properties, and high electrical conductivity. 16 Mo 2 C, in particular, has become a research focus due to its low cost and high hydrogen production efficiency. 17 However, producing well-defined nanostructures with a high density of catalytically active sites remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal carbides (TMCs), such as Mo 2 C, W 2 C, TiC, NbC, and VC, have broad application prospects in the field of energy storage and conversion due to their good thermal stability, mechanical properties, and high electrical conductivity. 16 Mo 2 C, in particular, has become a research focus due to its low cost and high hydrogen production efficiency. 17 However, producing well-defined nanostructures with a high density of catalytically active sites remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…The initial Volmer step involves the formation of M−H bond by decomposition of H 2 O in the alkaline medium followed by adsorbing hydrogen from the electrolyte in the second step liberating H 2 gas. 12 The small intrinsic series resistance (R s ) value of 0.89 Ω reflects the best electrical conductivity of the material, and also the small R ct value of 1.1 Ω indicates smaller chargetransfer resistance (Figure 5c). Moreover, the long-term chronoamperometry study of N10V7M3 achieving cathodic current density of around 10 mA cm −2 by applying −1.15 V over 24 h shows good retention indicating outstanding stability of the catalyst (Figure 5d).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In this regard, transition-metal nonoxides, especially transition-metal nitrides (TMNs), have attracted much attention because of their special characteristics, like outstanding electronic properties, electrical conductivity, corrosion resistance nature, and high chemical stability. 12 TMNs, for example, Ni 3 N, Co x N, and Fe x N, are often found to be much suitable toward HER mechanism. 13−16 Among these, Ni 3 N has shown much potential to be considered for both HER as well as UOR.…”
Section: ■ Introductionmentioning
confidence: 99%
“…15 Moreover, transition metal carbides, nitrides, selenides, and chalcogenides have also been used for OER and ORR electrocatalysis. 12,15,16 For example, Wei et al reported a composite electrocatalyst-integrated N-doped graphene and Co/Fe oxides, achieving an excellent performance with an ΔE of 0.78 V. 17 solution for efficient ORR/OER activity. Artificial intelligence (AI) and machine learning (ML) have brought brilliant solutions to this problem, which reveal patterns in training data using statistical models and optimization algorithms to make predictions or decisions.…”
Section: Introductionmentioning
confidence: 99%
“…The composite of carbon materials with transition metal oxides/hydroxides and heteroatom doping have been reported as bifunctional materials for OER/ORR in the alkaline electrolyte . Moreover, transition metal carbides, nitrides, selenides, and chalcogenides have also been used for OER and ORR electrocatalysis. ,, For example, Wei et al reported a composite electrocatalyst-integrated N-doped graphene and Co/Fe oxides, achieving an excellent performance with an Δ E of 0.78 V . Deng et al presented a single-atom catalyst of N-doped carbon with embedded Co/Ni, which delivered a superior bifunctional ORR/OER activity (Δ E = 0.81 V) .…”
Section: Introductionmentioning
confidence: 99%